Tadalafil has biologic activity in human melanoma. Results of a pilot trial with Tadalafil in patients with metastatic Melanoma (TaMe). (2nd September 2017) - Hassel, Jessica C.; Jiang, Huanhuan; Bender, Carolin; Winkler, Julia; Sevko, Alexandra; Shevchenko, Ivan; Halama, Niels; Dimitrakopoulou-Strauss, Antonia; Haefeli, Walter E.; Jäger, Dirk; Enk, Alexander; Utikal, Jochen; et al.
ABSTRACT: Myeloid-derived suppressor cells (MDSCs) are known to play a critical role in the suppression of T cell antitumor responses. Our preclinical data showed that the phosphodiesterase (PDE)-5 inhibitor sildenafil impaired MDSC functions, enhanced intratumoral T cell activity and prolonged survival of melanoma-bearing mice. In this study, we evaluated biologic effects, safety and efficacy of palliative treatment with the PDE-5 inhibitor tadalafil in metastatic melanoma patients. We conducted an open-label, dose de-escalation trial with tadalafil in pretreated metastatic melanoma patients. Tumor and peripheral blood samples were taken before and 4 weeks after the start of treatment. Samples were investigated by immunohistochemistry and FACS analysis, for different immune subsets with numbers of CD8 + tumor-infiltrating lymphocytes (TIL) as primary end point. Stable disease was achieved in 3/12 patients (25%). Median progression-free survival was 4.6 mo (range 0.7–7.1), median overall survival (OS) 8.5 mo (range 2.7–23.7). The treatment was well tolerated. Stable patients displayed significantly higher numbers of CD8 + TIL in the center of metastases before treatment as compared with progressive patients. Upon the therapy, they showed increased expression of ζ-chain (used as a marker of T cell activation) in CD8 + and CD4 + TILs and CD8 + T cells in the peripheral blood as compared with baseline. Our study suggests that the PDE-5 inhibitor tadalafil can improve clinical outcome of advanced melanoma patients by enhancing antitumor immunity and highlights its potential application in combined melanoma immunotherapy.